PRÁTICAS GERENCIAIS COMO INSTRUMENTO DE MELHORIA ORGANIZACIONAL: UM ESTUDO COMPARATIVO ENTRE UNIDADES PÚBLICAS DE SAÚDE QUE ADOTARAM OS CRITÉRIOS DO MEG, TENDO COMO FOCO O CRITÉRIO ESTRATÉGIAS E PLANOS. - Rosa, Meirelane Souza (2012)
This work had as general purpose to effect a comparative analysis of the management practices implemented by three public health Units which adopted the Management Excellence Model (MEG), focusing on the Strategys and Plans Criterion, what makes this work a multiple case study. To reach the proposed purpose, analyses of the management practices implemented were made seeking to know the reality of these institutions in order to notice why the implementation of the Model occured in a different way in these institutions, which factors effectively impacted in the development, alignment and monitoring of their Strategic Planning and, still, how the implementation of the MEG helped these instituitions in the continuos process of learning. The most significant changes occured in the last years were pointed out and, with that, it was possible to realize that the implementation of the Management Excellence Model was a determinant factor to aid the studied hospitals in the alignment of their processes, in the structuring and definition of their management practices and still aid the institutions to face new challenges and demands from Society.